UMA ECOLOGIA REFÉM DO PODER ECONÔMICO: Leitura exegética sócio-econômica de Deuteronômio 5,12-15 - Almeida, Fabio Py Murta de (2007)
There is an intention to establish a balance between human being and nature in the agricultural area of Judah, before the reign of Josiah (640-609 B.C.). In this in case that, the question could be if the sentence of Deuteronomy 5,12-15 would be an ecological speech? Frank Crüsemann and Haroldo Reimer admit part of the Old Testament laws had a destination in the group called people of the land of Judah that wanted the maintenance in the power. This group that would have assumed the leadership in Judah by means of a politician coup, since then, the people of the land had probably articulated a politic of alliance to conserve itself in the power even not assuming directly the power. They used a politic of alliances and implemented the sentence of Deuteronomy 5,12-15. It was written, by elders, group which the people of the land would have had an alliance so that they could command legal sentences for its social accommodation. In this case, in the gate of the city, way the quarrels, claims and proposals of intermediacies, it must have sentenced the use of techniques in the agriculture. The transport using big animals, whose weight harmed the small properties of Judah, must have been the reason of incessant small conflicts between e small and great land proprietors. Only few men of Judah could have access to these animals. This solution, as we understand, binds the caster of cultures to the rest of the pertaining field of the people in the land of Judah. Saturday, typical of the Babylonian empire is leagued to the term, with the life of the agricultural Jewish elite of the final period daily pre-exile. An exit found for the elites of Judah in which it takes us to ponder in a similar situation among Latin American, ahead of the challenges of the globalization. Therefore, if the text Deuteronomy 5, 12-15 is a balance of the hegemonic elites of Judah that searches the balance between human being and nature (ecology), the ecological speech contemporary will be able to have in this text an important interlocutor. This speech can occult economic interests, completely different; because it is about a dominator and not liberating strategy. The objective, over all, is for the social maintenance. In this in case that, Brazil and the other countries of Latin America have been suffering, for some time, because of this distance between the elite and the remaining portion of the society. Our elites uses the ecological speech to remain itself in the power of these societies. For example, we see in the reporters an amount of programs and news about the destruction of the nature. This is interesting, because, after having exactly destroyed the nature, they now pass to defend it; controlling the natural reserves, they guarantee its productivity and its status in the current economic system.(AU)